Strategic and Statistical Considerations on the QT Assessment of Volasertib. (July 2018) - Wallenstein, Gudrun; Walter, Beate; Fritsch, Holger; Taube, Tillmann
Volasertib is a selective cell cycle kinase inhibitor that induces mitotic arrest and apoptosis by targeting Polo-like kinase (Plk). A potential for prolonged QT intervals was indicated with volasertib in preclinical studies and preliminary clinical data. As a result, electrocardiograms (ECGs) have been collected in all volasertib clinical trials to monitor potential cardiac effects. This article describes strategic and statistical methods prospectively planned to perform an integrated analysis of ECG data from available trials to evaluate volasertib's effect on cardiac repolarization, as reflected by changes in the duration of QT interval and other ECG-related endpoints. Methods to effectively cope with heterogeneity between trials (ie, differences in study designs) are discussed. These strategies may be useful for other investigational drugs for which QT risk assessment is required, but a thorough QT/QTc trial is not feasible, resulting in the need for an alternative approach. Volasertib therapy relevantly prolonged adjusted mean QTcF change from administration baseline following the first and subsequent infusions. The integrated analysis revealed that the volasertib effects on the mean QTc changes from baseline were transient and had resolved at 24 hours after start of the first infusion. There was no evidence for a long-term impact on the QTcF interval following multiple infusions with volasertib.